Enhancing Nutrient Uptake and Economic Return of Fenugreek through Different Herbicides Application - Vikash Meena; M. L. Mehriya; Anuj Kumar; U. N. Shukla (Annals of Arid Zone, 2025)
A field experiment was conducted to study the effect of different herbicide on nutrient uptake in fenugreek at experimental field of the Agricultural Research Station Mandor, Jodhpur during winter (rabi) season of 2021-22. The study included ten treatment combinations of herbicides of which four namely Pendimethalin, Pendimethalin + Imazethapyr, Diclosulam, Flumioxazin were applied pre-emergence while four others viz. Imazethapyr, Sodium aciflurofan + Clodinafop propargyl, Fomesafen + Fluazifop p-butyl, Fluazifop p-butyl were applied 20 days after sowing. Additionally, a manually maintained weed-free plots and a weedy check plot were also maintained for comparison. Among the various treatments tested, the combination of Pendimethalin + Imazethapyr was particularly effective, resulting in significantly higher seed and straw yields of 1652 kg ha-1 and 4041 kg ha-1, respectively. This treatment also enhanced nitrogen content and uptake in both seeds (3.169% and 52.35 kg ha-1) and straw (0.998% and 40.33 kg ha-1), while yielding net returns of Rs. 79,162 ha-1 and a benefit-to-cost (B:C) ratio of 4.32 for fenugreek cultivation.